Pengaruh Latihan Resistance Ekstremitas Bawah Dengan Metode Dumbbell Squat Terhadap Peningkatam Vertikal Jump Pada Atlet Bola Voli Di Jpok Universitas Negeri Sebalas Maret Surakarta - Fauzan, Miftah, Totok Budi Santoso, S.Fis, Arif Pristianto, SSt.FT.,M.Fis (2016)
Background: Jumping ability is one of the most important determinants of performance in volleyball. In the volleyball match game, vertical jumps are performed frequently, setting and attacking players performing at least one jumping movement during a 12 s rally. Moreover, frontcourt players perform approximately four block jumps and three spike jumps, each of the players averaging nearly 22 jump and landings per game. It was determined that volleyball players of better performing teams have higher vertical jump values. Aims of Research: To know effect ofresistance training lower extremity with the dumbbell squat method on vertical jump improvement in volleyball player at JPOK Sebelas Maret University of Surakarta. Research Method: This research applies method pre-experimental, with approach of pre and post test one group design. Number of samples at this research 15 sample. Way of sampling applies method purposive sampling. Result: Statistical test applies wilcoxon result of that significant with value p 0,001 (<0,05). Conclusion: There is a significant effect resistance training lower extremity with the dumbbell squat method on vertical jump improvement in volleyball player at JPOK Sebelas Maret University of Surakarta. Keywords: Resistance training, Dumbbell Squat, Vertical Jump (VJ).